2022
DOI: 10.3168/jds.2021-20862
|View full text |Cite
|
Sign up to set email alerts
|

Transition cow nutrition and management strategies of dairy herds in the northeastern United States: Part I—Herd description and performance characteristics

Abstract: Our objective was to describe management and herd characteristics of the transition period on freestall dairy herds in the northeastern United States using an on-farm survey and prospective cohort design. Enrolled herds (n = 72) had a median of 900 milking cows (range: 345-2,900) and a rolling herd average of 12,674 kg (standard deviation ± 1,220 kg), and 87.2% (n = 82/94) of fresh pens were milked at least 3×/d. The prevalence of herds with ≥15% of sampled cows with elevated concentrations of nonesterified fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…For example, infections and inflammations can be detected by measuring the rectal temperature. As part of regular monitoring of fresh cows, between 36% and 89% of farmers reported that rectal temperature was measured daily [ 12 , 19 , 26 ]. In this study and due to the SOP that all cows had to be measured at the initial examination, the measurement of the rectal temperature was also the most frequent procedure (56% of all conducted examinations).…”
Section: Discussionmentioning
confidence: 99%
“…For example, infections and inflammations can be detected by measuring the rectal temperature. As part of regular monitoring of fresh cows, between 36% and 89% of farmers reported that rectal temperature was measured daily [ 12 , 19 , 26 ]. In this study and due to the SOP that all cows had to be measured at the initial examination, the measurement of the rectal temperature was also the most frequent procedure (56% of all conducted examinations).…”
Section: Discussionmentioning
confidence: 99%
“…A more in-depth description of the study population and study design was previously published ( Kerwin et al, 2022b ). Briefly, a retrospective cohort study was conducted from a convenience sample of 72 farms located in New York and Vermont between November 2012 and August 2015.…”
mentioning
confidence: 99%
“…Health event records, reproductive records, and milk records were acquired through the farm's record management software program when all sampled cows were at least 150 DIM. A more complete description of health disorder definitions were described previously ( Kerwin et al, 2022b ).…”
mentioning
confidence: 99%
See 2 more Smart Citations